The Development of Diazinon Sensors using Polyvinyl Alcohol (PVA) Membrane CuO on Surface Screen-Printed Carbon Electrode (SPCE) as a Receptor - Anisa Resti; Ani Mulyasuryani; Diah Mardiana (The Journal of Pure and Applied Chemistry Research, 2019)
The development of Diazinon sensor has been studied using polyvinyl alcohol (PVA-CuO membrane on the surface of the screen-printed carbon electrode (SPCE) as a receptor. The membrane used consisted of polyvinyl alcohol (PVA) 5% (w/v), citric acid 5% (w/v), glutaraldehyde 4% (v/v), Diazinon solution 40 ppm (v/v), and CuO 5% (w/v). This study established the effect of Diazinon at 0.01,0.02 and 0.03 (w/w). besides, the concentration of CuO was 0.5 and 1 (w/w). Signal measurements were carried out in the concentration range of the Diazinon 10-12 - 10-5 M solution in Britton-Robinson buffer at pH 2 - 5. Besides, the influence of the electrolyte type was studied using HCl pH 4, 10-5 M KCl, pH 3 phosphate, and phosphate-KCl pH 3 buffers. The results of the Diazinon sensor characterization showed that the highest sensitivity was obtained at 42 mV/decade with a response time of 180 seconds.